Paciente masculino de 76 años de edad con diabetes mellitus tipo 2 e hipertensión. - Welligton Franco, Mario Medardo (2020)
The present clinical case is an adult over 76 years of age, has 3 children and lives in windows, with a history of high blood pressure 10 years ago, his treatment consists of losartan of 100mg one a day, indicates that he does not follow recommendations of diet or physical activity, surgical history does not present, within the family pathological history, the mother suffered from type 2 diabetes mellitus, patient goes to routine control in what refers that the last week has presented muscle pain, numbness of the hands , tired, very hungry and very thirsty at night, afraid of suffering from hypertension since his mother died of that disease; The nutritional assessment of the patient is carried out and his BMI reflected a normal weight without cardiovascular risk, the corresponding biochemical tests were performed and his results reflected, hyperglycemia, ypercholesterolemia and hypertriglyceridemia, after performing all the complementary examinations he is diagnosed with type diabetes 2 and is referred to the nutritionist for intervention. An individualized nutritional plan is carried out to the patient, taking into account their socioeconomic situation and their pathological condition, the type of diet that will be prescribed will be the DASH diet, divided into 5 meals a day, characterized by being a diet, rich in potassium, low in sodium, and high in fiber that will help stabilize the blood sugar levels and blood pressure of the patient. A patient follow-up and monitoring plan is carried out in a month, where favorable results were observed in the patient's health condition.